What Is New in Minimally Invasive Surgery?: Best Articles From the Past Year. Issue 3 (March 2017) - Hurd, William W.
Abstract : Minimally invasive hysterectomy has a number of well-documented advantages compared with open hysterectomy, including lower complication rates, lower cost, and faster recovery. In this retrospective study of almost 10, 000 women undergoing minimally invasive hysterectomy for endometrial cancer, the investigators found that laparoscopic compared with open hysterectomy was associated with a decreased risk of venous thromboembolism (0.7% vs. 2.2%, respectively; P <.001). This relationship remained after correcting for age, body mass index, race, operative time, comorbidity index, and surgical complexity. It was assumed that the majority of these patients undergoing surgery for cancer received some form of venous thromboembolism prophylaxis.